SMART AGRICULTURE BASED IOT AND MOBILE APPS - Somantri; Supriatna; Hardi Herdiana; Ujang Mulyana; Anggy Pradifta Junfithrana (Nusa Putra University, 2020)
Agriculture is the main occupation in our country for many centuries. But now because of the migration of people from rural to urban areas there are barriers to agriculture. So to solve this problem we are using smart farming techniques using IOT. Smart farming is a developing concept, because the IOT Sensor is able to provide information about the agricultural sector and then act on user input. To develop this Intelligent Agricultural System, it uses the advantages of the latest technology such as Arduino, IOT and Wireless Sensor Networks. The paper aims to make use of the emerging technology namely IOT and the use of intelligent agricultural automation. Monitoring of environmental conditions is the main factor for increasing efficient crop yields. This feature includes the development of a system that can monitor temperature, humidity and is programmed via an android application.